Electoral turnout during states of emergency and effects on incumbent vote share - Marco Frank; David Stadelmann; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2020)
In March 2020, the second ballot of local elections in the German state of Bavaria was held under an official state of emergency due to the Covid-19 pandemic. Bavarian mayors are elected by majority rule in two-round (runoff) elections. Between the first and second ballot of the election, the state government announced a state of emergency with drastic measures to fight the spread of Covid-19, including a shutdown of public life and restrictions to individual mobility. We employ a difference-in-difference setting to contrast turnout of the first and second ballot in 2020 with the first and second ballots from previous elections. The state of emergency led to an increase in turnout of 10 percentage points. This increase in turnout is robust and there is no relevant heterogeneity of the increase across municipalities. We argue that voting is an act of identifying with the collectivity of society which seemed to increase under adverse circumstances. In addition, the emergency induced higher turnout from the difference-in-difference setting is employed as an instrument to analyze the effect of turnout on the vote share of incumbents. Controlling for party affiliations and other factors, the results indicate that incumbents tend to profit marginally from higher turnout.
Keywords: D72; 330; Covid-19; turnout; mayoral elections; voting in crises